Morphological and anatomical features of Leucojum aestivum L. (lower reaches of the Dnieper, Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
The article describes an ornamental and medicinal plant − Leucojum aestivum, that was included to the Red Data Book of Ukraine. L. aestivum is a perennial herbaceous of the family Amaryllidaceae. The natural habitat of the species includes the Mediterranean, European temperate climate regions (except of northeastern one), the Caucasus. L. aestivum is a hardy species that is very moisture-tolerant. It is extremely tolerant of soil type and will grow in sand, loam and clay soils although it prefers soils with a more neutral or alkaline pH. The morphological and anatomical features of the underground and surface structure were investigated; the model of formation shoots, the types of buds and seasonal rhythm of L. aestivum were described in the modern south of Ukraine.
Keywords: Leucojum aestivum, bulb, leaf, stem, flower, shoot.